Guide to performance-based road maintenance contracts. (Asian Development Bank, 2018)
This guide serves as a reference for implementing performance-based road maintenance contracts in Central Asia Regional Economic Cooperation (CAREC) countries to promote effective and efficient maintenance of road networks.